2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33143
|View full text |Cite
|
Sign up to set email alerts
|

On Transfer Student Success: Exploring the Academic Trajectories of Black Transfer Engineering Students from Community Colleges

Abstract: Dr. Bruk T. Berhane received his bachelor's degree in electrical engineering from the University of Maryland in 2003. He then completed a master's degree in engineering management at George Washington University in 2007. In 2016, he earned a Ph.D. in the Minority and Urban Education Unit of the College of Education at the University of Maryland. Bruk worked at the Johns Hopkins University Applied Physics Laboratory, where he focused on nanotechnology, from 2003 to 2005. In 2005 he left JHU/APL for a fellowship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In 2000, as many as 40% of students who received a bachelor's or master's degree in engineering attended a community college at some point [47]. Several studies have shown that transfer students are equally or more successful compared to non-transfer students in completing degrees in engineering [104], [105], [106]. Thus this student group is key to growing the quantum workforce.…”
Section: Transfer Pathways From Two-year and Four-year Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, as many as 40% of students who received a bachelor's or master's degree in engineering attended a community college at some point [47]. Several studies have shown that transfer students are equally or more successful compared to non-transfer students in completing degrees in engineering [104], [105], [106]. Thus this student group is key to growing the quantum workforce.…”
Section: Transfer Pathways From Two-year and Four-year Institutionsmentioning
confidence: 99%
“…IV-B. It is important to engage 2-year and 4-year institutions without engineering programs to open up transfer pathways [104], [105], [106].…”
Section: E Summary Of Diversity Equity and Inclusion Recommendationsmentioning
confidence: 99%
“…Scholarship on international graduate students in the U.S often do not focus on undergraduate experiences earned in students' home countries. Across the spectrum of studies on Black engineering students [5], [10]- [15] in the U.S., research has generally not explored the undergraduate experiences of foreign-born Blacks in their home countries. Given the considerable intellectual capital that WAFR engineering students, and particularly Nigerian engineering students, bring to the U.S., and their contributions to the workforce [16], further study of their academic pathways (before and after transitioning to the U.S.) is valuable.…”
Section: Nigerian Engineering Studentsmentioning
confidence: 99%
“…Wang [51] highlighted community college transfer students as a heterogeneous group and that administrators and faculty at four-year universities should consider students' gender and other demographic differences in implementation of policies and strategies [24]. Understanding how to increase and build transfer student capital supports a variety of different types of transfer pathways that are not only an important way to increase diversity in engineering programs of study but equally as important in helping students successfully persist through the pathway to a degree and into the workforce [1], [8], [52].…”
Section: Impact Of Transfer Student Capital On Stem and Engineering E...mentioning
confidence: 99%
“…Next, the research in this study extended to include articles that were not specifically focused on engineering but more broadly included transfer student capital with transfer students across disciplines and in the broader STEM contexts. Inclusion of these articles provided a broader understanding for transfer students across engineering and related fields because there is a larger volume of published literature on STEM transfer students [52], [53]. Additionally, inclusion of these articles was beneficial because of the large overlap of engineering and STEM and the additional knowledge that the general articles were able to provide in an area of scant but emerging engineering education research.…”
Section: Limitationsmentioning
confidence: 99%